Frequency and predictors of thin-cap fibroatheroma progression: a comprehensive and dynamic in-vivo OCT study. (14th October 2021) - He, L; Xu, Y; Hu, S; Qin, Y; Weng, Z; Feng, X; Zhao, C; Zeng, M; Chen, X; Yi, B; Xie, C; Zhang, D; et al.
Abstract: Purpose: To assess the evolution of thin-cap fibroatheroma (TCFA) and to explore predictors for its progression by using optical coherence tomography (OCT) in patients with acute coronary syndrome (ACS). Methods: We enrolled ACS patients with non-culprit TCFA at baseline and corresponding OCT images at follow-up of 9 to 15 months. Clinical, angiographic and OCT data were collected and analyzed according to established methods. TCFA was defined as a lipid plaque with maximum lipid arc >90° and fibrous cap thickness <65μm. Considering the resolution of OCT, the regression of TCFA was defined as an increase of fibrous cap thickness >10μm. Inversely, TCFA progression was defined as a decrease, constant or ≤10μm increase of fibrous cap thickness. Results: 41 patients with 55 non-culprit TCFAs were taken into final analysis. 17 patients (41.5%) had patient-level progression and 22 TCFAs (40.0%) progressed at plaque-level with a median follow-up duration of 371 days. 11 (20.0%) of the 55 TCFAs happened subclinical rupture at follow-up, including 10 with the formation a new layer and 1 without the detection of the new layer. Besides, another patient suffered re-myocardial infarction because of the rupture of TCFA induced acute thrombosis and lumen occlusion during follow-up. The baseline clinical and angiographic characteristics were similar between the two cohorts. The progression group had a significantly higher prevalence of macrophage infiltration and vasa vasorum at baseline than the non-progression group (Figure 1). Multivariate analysis identified macrophage infiltration (odds ratio [OR]: 5.30; 95% confidence interval [CI]: 1.01 to 27.91; p=0.049]) as the independent predictor of TCFA progression. When it came to the evolution of lesion morphology and lipid components, the progression cohort had a higher percent change of lumen stenosis and lipid length (Figure 2). Conclusions: About 40% of non-culprit TCFAs in ACS patients progressed in fibrous cap thickness at a median interval of 1 year. Macrophage infiltration was the independent predictor of non-culprit TCFA progression. The progression of fibrous cap thickness was usually accompanied with an aggressive evolution of other lesion characteristics. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): the National Key R&D Program of China